If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3x = 2(x + 3) Combine like terms: 2x + 3x = 5x 5x = 2(x + 3) Reorder the terms: 5x = 2(3 + x) 5x = (3 * 2 + x * 2) 5x = (6 + 2x) Solving 5x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5x + -2x = 6 + 2x + -2x Combine like terms: 5x + -2x = 3x 3x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 3x = 6 + 0 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 28(x-7)=44(x-11) | | 8x-3y=13fory | | 5p-8=-13 | | 3/5-35 | | 32=x+17 | | 6/5+5x=14/5-6x | | 6x+7=6(x-3) | | 4ln(3x+7)=12 | | 237-6x=39x+22 | | (x-2)/2=5x | | 9-7x=77-21x | | x=4y-28 | | 24=X+5 | | 0.10(y-6)+0.16y=0.02y-0.03(60) | | X+22=17 | | x/n=r | | 5(x-2)+6= | | 9x-6=10x-21 | | 9x^2y+15xy^2=0 | | 2x^2-13-70=0 | | -80=8(x-7) | | -41+5w=34+10w | | 16=8/w | | 8(x-8)-8=-72 | | W-7.89=2.19 | | 2/5+2x=5 | | 20-3x=4(-2x-5) | | 6x-14-9x+11=12x-16 | | x-0.25=451.50 | | 4(5m+4)=176 | | 5/13x=-9 | | -1r=-3r+2r |